2020
DOI: 10.1111/1759-7714.13672
|View full text |Cite
|
Sign up to set email alerts
|

Oncological advantage of nonintubated thoracic surgery: Better compliance of adjuvant treatment after lung lobectomy

Abstract: Background Video‐assisted thoracoscopic (VATS) surgery contributes to improved survival, adjuvant chemotherapy delivery and less postoperative complications. Nonintubated thoracic surgery (NITS) VATS procedures improves immunological responses in lung cancer patients; however, there is no data regarding adjuvant chemotherapy delivery effectiveness following NITS lobectomies. In this study, we aimed to compare protocol compliance and toxic complications during adjuvant chemotherapy after intubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…Considering the oncological adequacy of NITS procedures, most of the studies dealing with NITS major lung resections reported no significant differences about lymph node dissection; only one of the above reported studies showed a significant difference regarding the The study reported an oncological advantage in NITS patients, showing better compliance with therapy protocols and fewer events of toxicity: these results can be related to a better physiological inflammatory and cellular immune response and fewer immunodepressive effects after a less invasive surgical procedure and a shorter hospital stay. Even though further studies are needed to investigate the relation of NITS and oncological advantages after surgery in NSCLC, these results support the benefits of minimal invasiveness on adjuvant chemotherapy (29).…”
Section: Discussionmentioning
confidence: 66%
“…Considering the oncological adequacy of NITS procedures, most of the studies dealing with NITS major lung resections reported no significant differences about lymph node dissection; only one of the above reported studies showed a significant difference regarding the The study reported an oncological advantage in NITS patients, showing better compliance with therapy protocols and fewer events of toxicity: these results can be related to a better physiological inflammatory and cellular immune response and fewer immunodepressive effects after a less invasive surgical procedure and a shorter hospital stay. Even though further studies are needed to investigate the relation of NITS and oncological advantages after surgery in NSCLC, these results support the benefits of minimal invasiveness on adjuvant chemotherapy (29).…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, a recent study from our group by Furák et al found oncological benefits with the NITS method, as a significantly greater proportion of non-intubated patients was able to complete the planned adjuvant chemotherapy and significantly less toxicity and neutropenia occurred among them (8).…”
Section: Advantages Of Nitsmentioning
confidence: 88%
“…Traditionally, video-assisted thoracic surgery (VATS) procedures require general anesthesia, muscle relaxation, and controlled ventilation with lung isolation. In recent years, the increasingly researched non-intubated techniques have become a safe and feasible alternative, with a less intense immunological response (5-7) and better oncological compliance (8). The key anesthetic consideration behind the non-intubated technique is the maintenance of spontaneous breathing with its advantageous effects on respiration during thoracoscopic or even open thoracic procedures (9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic development of the spontaneous ventilation VAT S h a s b e e n a c c u r a t e l y d e s c r i b e d ( 1 0 ) . T h e anaesthesiological proportion has been clearly evaluated (11,12) and the oncological aspect of the method is finally emerging (13). Many particular approaches through the appropriate thoracic region into the relevant intrathoracic field are widely documented in current literature (14).…”
Section: The Proceduresmentioning
confidence: 99%